About That: Deploying and Deploring Sex in Postsoviet Russia - Eliot Borenstein (Studies in 20th & 21st Century Literature, 2000)
Desovietization brought sex as a visible cultural phenomenon into Russia, one rife with contradictions and conflicts. Newspapers, popular magazines, advertisements, pornography, the first Russian sex talk show (About That), and pronouncements by a broad range of quotable public figures indicate that the problematics of sex during the 1990s consisted of the following: a sexualized relationship between Russia and the West; a sexualization of politics (rather than the politicization of sex); an inflexible yet implicit code governing the deployment of sex in "high" and "low" culture; and, above all, the development of a sexual discourse that defied circumlocution and repression even as it relied on them. Whereas during the early 1990s Russia seemed content to learn and borrow from Western sexual discourse, by mid-decade sexuality became a forum for nationalist fervor, articulated in terms of international relations.
Keywords: desovietization; sex; culture; Russia; conflict; About that; sexualization of politics; sexual discourse; circumlocution; repression; international relations